Evaluating the efficacy and safety of tebentafusp in the treatment of metastatic uveal melanoma: a 2025 update systematic review and meta-analysis - Wang, Yanlin; Sun, Wen; Wang, Bing (Frontiers in Oncology, 2025)
BackgroundMetastatic uveal melanoma (mUM) is an aggressive malignancy with a dismal prognosis, posing a severe threat to patients’ survival and quality of life. In recent years, tebentafusp, a novel immunotherapeutic agent, has demonstrated promising potential in the management of mUM. However, inconsistencies and controversies persist in the findings of related research. This meta-analysis seeks to synthesize existing studies to more comprehensively and accurately assess the efficacy (with a primary focus on overall survival [OS]) and safety of tebentafusp in treating this disease.MethodsSystematic searches were conducted across databases including PubMed, Embase, and the Cochrane Library. Literature screening was performed rigorously in line with predefined inclusion and exclusion criteria, while the quality of included studies was assessed using the Minors scale. To ensure accuracy, data extraction was carried out independently by two researchers.ResultsThis meta-analysis included 18 studies meeting predefined criteria, encompassing patients with mUM treated with tebentafusp. These comprised 3 randomized controlled trials (RCTs) and 15 single-arm studies, with sample sizes ranging from 10 to 252 participants, and most patients being HLA-A*02:01 positive. The pooled complete response (CR) rate across 3 studies was 0.01 (1%, 95%CI: -0.01 to 0.01, p=0.18). For 15 studies, the pooled partial response (PR) rate was 0.07 (7%, 95%CI: 0.06 to 0.09, p<0.00001), and the pooled stable disease (SD) rate was 0.34 (34%, 95%CI: 0.26 to 0.41, p<0.00001), though significant heterogeneity was observed for SD (I²=84%).Across 15 studies, ORR ranged from 4.7% to 21.7%, with a pooled rate of 0.07 (7%, 95%CI: 0.06 to 0.09, p<0.0001) and low heterogeneity (I²=34%).For 16 studies, the pooled DCR was 0.46 (46%, 95%CI: 0.40 to 0.53, p<0.0001) with significant heterogeneity (I²=77%).The pooled 1-year overall survival (OS) rate across 9 studies was 0.69 (69%, 95%CI: 0.66–0.72, p<0.0001); the 2-year OS across 3 studies was 0.42 (42%, 95%CI: 0.38–0.46, p<0.0001); and the 3-year OS across 2 studies was 0.26 (26%, 95%CI:0.21–0.30, p<0.0001). Pooled median progression-free survival (PFS) across 10 studies was 2.74 months(95%CI: 2.58–2.90), and median OS across 4 studies was 19.78 months(95% CI:17.79–21.77). The pooled incidence of grade ≥3 treatment-related adverse events (TRAE) across 7 studies was 0.40 (40%, 95%CI:0.16–0.63, p=0.001) with high heterogeneity (I²=98%).The pooled incidence of cytokine release syndrome (CRS) across 8 studies was 0.86 (86%, 95%CI: 0.83–0.89, p<0.0001) with moderate heterogeneity (I²=54%). Subgroup analysis showed patients with no previous treatment received had higher PR (0.11 vs. 0.06 in previously treated patients), ORR (0.11 vs. 0.07 in previously treated patients), 1-year OS (0.72 vs. 0.63 in previously treated patients), and 2-year OS (0.45 vs. 0.39 in previously treated patients).ConclusionsTebentafusp exhibits significant clinical efficacy in mUM, with its greatest value reflected in improving long-term survival (1-year, 2-year, and 3-year OS) — a finding consistent with its FDA approval basis. While ORR and DCR provide supplementary evidence of therapeutic benefit, radiological response rates (e.g., CR, PR) are limited in fully capturing its clinical value. Safety concerns include high CRS incidence (mostly low-grade and manageable) and variable grade ≥3 TRAE rates. No previous treatment received patients may derive greater benefits. Limitations (heterogeneity, HLA-A*02:01 restriction, limited long-term data) highlight the need for more high-quality studies to validate long-term efficacy/safety, expand applicability to broader populations, and explore combination therapies. Additionally, circulating tumor DNA (ctDNA) may serve as a more sensitive efficacy biomarker than radiological responses, warranting further investigation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251084090.